ANALISIS PENGONTROLAN DAN MONITORING PERANGKAT ELEKTRONIK BERBASIS JARINGAN INTERNET MENGGUNAKAN EDIMAX SP-1101W DENGAN APLIKASI EDIPLUG - ., Silvia Budi Ratnasari (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
Edimax SP-1101W Smart Plug Switch is a tool to turn off and turn on the electric controlled remotely via smartphone using Ediplug application. Electronic devices that are connected to Edimax SP-1101W Plug Smart Switch as research material that is lamp and fan. From the results of research can be summed process control and monitoring can be done anywhere as available internet networks. The  outcome  average  of internet  access  speed  on  researcher?s  home  area was  0,292  Mbps  for downloading, 0,768 Mbps for uploading and ping (delay) is 178 ms. If compared to the TIPHON standard, ping value in the category of "good" because its value is between 150 s / d 300 ms. As for the ITU-T standard, ping value in the category of "moderate" because its value is between 150 ms s / d to 400 ms. Besides, the outcome average of internet access speed on  Telecommunications Laboratory of Engineering Faculty at Tanjungpura University area 0,082 Mbps for downloading, 0,001 Mbps for uploading and ping (delay) is 2.674 ms. If compared to the TIPHON standard, ping value in the category of "bad" because its value is above 450 ms. As for the ITU-T standard, ping value in the category of "bad" because its value is above 400 ms. Factors that influence the process of controlling and monitoring is the quality of network service smartphone in location research, quality of network services from access Edimax BR-6428NS V2 N300 Multi-Function Wifi Router, distance and the obstacles.   Key words: Controlling and Monitoring, Ediplug, Access Speed